Learning to adapt: educational technologies and the construction of sustainable and resilient learning environments - Boustani, Nada Mallah; Mourtajji, Loubna; Arts-Chiss, Nathalie (Frontiers in Education, 2026)
IntroductionThis study examines the adaptability and resilience of undergraduate students at a French university during an abrupt transition to online learning triggered by a crisis. Grounded in resilience theory and the Technology Acceptance Model (TAM), the research investigates students’ perceptions of digital learning environments and their capacity to cope with academic disruption. It further situates the analysis within Connectivism and Technological Pedagogical Content Knowledge (TPCK) frameworks to assess the transformative potential of information and communication technologies (ICTs) in fostering inclusive and equitable education.MethodsA post-crisis quantitative survey was administered to 402 students enrolled at the Institut Universitaire de Technologie (IUT) in Oise. The questionnaire captured students’ experiences, emotional responses, and perceptions of online learning practices during the crisis. Factor analysis was conducted on key survey items (Q7) to identify underlying dimensions related to digital learning experiences.ResultsThe factor analysis revealed three principal dimensions shaping students’ learning experiences: teacher innovation in digital pedagogy, students’ emotional responses, and practical challenges associated with online learning. The findings indicate that social support networks and engagement in virtual communities played a significant role in helping students manage academic difficulties. Moreover, learning perceptions differed according to the level of study, with master’s students demonstrating higher levels of engagement and adaptability compared to undergraduates.DiscussionThe results underscore the critical role of pedagogical innovation, emotional support, and technical infrastructure in building sustainable and resilient digital learning environments. ICTs emerge not merely as tools for ensuring instructional continuity in times of crisis, but as enablers of pedagogical equity and institutional transformation. This study contributes to ongoing debates on sustainable and inclusive education by highlighting how well-supported digital ecosystems can enhance resilience and accessibility within higher education.